Assessment of Reading Comprehension in Primary Education: Reading Processes and Text - Mohamedi-Amaruch, Amaruch; Rico-Martín, Ana M. (Lenguas Modernas, 2020)
In this paper, the authors evaluate the reading skills of students finishing Primary Education in the Autonomous City of Melilla (Spain), and analyse the relation between the degree of ‘reading comprehension’ and the different ‘reading processes’ (literal, reorganizational, inferential and critical), as well as the relation with the texts employed in the study (literary, informative and interpretative). In order to achieve this, empirical-analytical research has been carried out, with an ex-post-facto descriptive study using a sample of 620 Year 6 students from ten schools, to which the ACL-6 test was applied. It is concluded that only 30% of the students surpass the comprehension level corresponding to their age. More than half have difficulty in all the ‘reading processes’, slightly fewer in the ‘literal’, and the degree of ‘comprehension’ is similar in the different types of text worked with, although worse in the ‘informative’ and ‘interpretative’.